Pelatihan Agen Toleransi bagi Generasi Z di Era Disrupsi: Religious Tolerance Agent Training for Generation Z in the Era of Disruption - Manuain, Leryani Mince Maria; Moru, Osian Orjumi; Renda, Trijuliani; Hauteas, Nikson (Amalee: Indonesian Journal of Community Research and Engagement, 2022)
Generation Z as active internet users has the potential to be exposed to radicalism issues which then have an impact on intolerance, especially in this era of disruption. Tolerance agent training for Generation Z which is carried out aims to increase understanding of religious tolerance, so that Generation Z can become agents of change in society in order to create a tolerant Indonesian society. Specifically, the delivery of material in this PkM activity was carried out by means of lectures, questions and answers, games, and individual exercises. The results of the PkM activities showed that 96.4% of participants understood the material presented, 98.8% of participants' satisfaction with the implementation of the activities, and 83% of participants' readiness to become tolerance agents. Based on these data, it can be concluded that there is an increase in participants' understanding of religious tolerance and the readiness of participants to become agents of religious tolerance.